Proteins with RNA Chaperone Activity: A World of Diverse Proteins with a Common Task—Impediment of RNA Misfolding - Katharina Semrad (Biochemistry Research International)
Proteins with RNA chaperone activity are ubiquitous proteins that play important roles in cellular mechanisms. They prevent RNA from misfolding by loosening misfolded structures without ATP consumption. RNA chaperone activity is studied in vitro and in vivo using oligonucleotide- or ribozyme-based assays. Due to their functional as well as structural diversity, a common chaperoning mechanism or universal motif has not yet been identified. A growing database of proteins with RNA chaperone activity has been established based on evaluation of chaperone activity via the described assays. Although the exact mechanism is not yet understood, it is more and more believed that disordered regions within proteins play an important role. This possible mechanism and which proteins were found to possess RNA chaperone activity are discussed here.